A head-to-head comparison of humoral and cellular immune responses of five COVID-19 vaccines in adults in China - Xu Han; Hongxing Pan; Pengfei Jin; Mingwei Wei; Siyue Jia; Wenjuan Wang; Kai Chu; Shuyu Gao; Li Zhou; Jingxin Li; Jingxin Li; Fengcai Zhu; et al. (Frontiers in Immunology, 2024)
IntroductionVarious COVID-19 vaccine trials have shown that vaccines can successfully prevent symptomatic cases of COVID-19 and death. Head-to-head comparisons help to better understand the immune response characteristics of different COVID-19 vaccines in humans.MethodsWe randomly selected 20 participants from each of five ongoing Phase II trials of COVID-19 vaccines. Here, SARS-CoV 2-specific immune responses to DNA vaccine (INO-4800), mRNA vaccine (BNT162b2), Adenovirus-vectored vaccine (CONVIDECIA), Protein subunit vaccine (Recombinant COVID- 19 Vaccine (Sf9 Cells)), Inactivated Vaccine (KCONVAC) were examined longitudinally in healthy adults between Jan 15, 2021 and July 5, 2021 for 6 months. RBD-IgG titres were detected by ELISA, neutralising antibody titer were detected by pseudoviral neutralization and immune cell response were detected by flow cytometry.ResultsAt the first visit (V1), 100% of individuals who received the BNT162b2, CONVIDECIA, or KCONVAC vaccines experienced seroconversion of neutralizing and binding antibodies in the serum. Except for the Recombinant COVID-19 Vaccine (Sf9 Cells) vaccine having the highest neutralizing antibody GMT at the second visit (although there was no statistically significant difference in geometric mean titers between V1 and V2), the rest of the vaccines had the highest levels of binding antibodies and neutralizing antibodies at V1. The neutralizing antibodies GMT of all vaccines showed a significant decrease at V3 compared to V1. The neutralizing antibody GMT against the omicron variant of all vaccines at V1 showed a significant decrease compared to the wild strain. We observed statistically significant differences in Tcm cells and RBD-specific memory B cells among various vaccines.DiscussionBNT162b2 (mRNA vaccine) exhibits the highest antibody levels among the five vaccines evaluated, regardless of whether the target is the wild-type virus or its variants. However, its cellular immune response may be weaker compared to CONVIDECIA (adenovirus type 5 vector vaccine).